2010
DOI: 10.1152/ajpgi.00077.2010
|View full text |Cite
|
Sign up to set email alerts
|

The islet-acinar axis of the pancreas: more than just insulin

Abstract: Although the role of the islets in the regulation of acinar cell function seemed a mystery to investigators who observed their dispersion among pancreatic acini, over time an appreciation for this intricate and unique structural arrangement has developed. The last three decades have witnessed a steadily growing understanding of the interrelationship of the endocrine and the exocrine pancreas. The islet innervation and vascular anatomy have been more fully characterized and provide an appropriate background for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 207 publications
(197 reference statements)
5
83
1
4
Order By: Relevance
“…islet-acinar communication (28); hence, we studied normoglycemic mice to minimize confounding effects of increased insulin secretion. Evidence against a role for insulin as an indirect GLP-1R-dependent stimulator of pancreatic protein synthesis and mass derives from studies using genetic selective restoration of hGLP1R expression in murine b-cells of Glp1r 2/2 mice (14).…”
Section: Discussionmentioning
confidence: 99%
“…islet-acinar communication (28); hence, we studied normoglycemic mice to minimize confounding effects of increased insulin secretion. Evidence against a role for insulin as an indirect GLP-1R-dependent stimulator of pancreatic protein synthesis and mass derives from studies using genetic selective restoration of hGLP1R expression in murine b-cells of Glp1r 2/2 mice (14).…”
Section: Discussionmentioning
confidence: 99%
“…A complex 'insulo-acinar portal system' (Williams & Goldfine 1985) supplies the exocrine part of the pancreas with blood coming from the islets and is thus rich in insulin but also in glucagon, somatostatin, and other molecules secreted by the endocrine pancreas. This implies that functions of the exocrine pancreas may be regulated by the hormones of the endocrine pancreas (Barreto et al 2010). Evidence suggests that insulin regulates both growth and function of the exocrine pancreas.…”
Section: How Do Igf and The Insulin Systems Cooperate And Collaboratementioning
confidence: 99%
“…It is known that diabetic patients under insulin therapy suffer from impairment of the exocrine pancreatic function (Lankisch et al 1982). In rats and mice, it has been demonstrated that insulin regulates amylase secretion (Barreto et al 2010) via IRs expressed on the acinar cells (Mossner et al 1984, Okabayashi et al 1989. Taken together, exposure of the exocrine pancreas to higher insulin concentrations as well as the presence of the receptor tyrosine kinases IR and IGFR in the exocrine pancreas might lead to the idea that exocrine cells are exposed to a high mitogenic challenge that can be of crucial importance for cancer development and its progression.…”
Section: How Do Igf and The Insulin Systems Cooperate And Collaboratementioning
confidence: 99%
“…Animal studies of the effect of diabetes on the exocrine pancreas have primarily been carried out using the beta cell toxin streptozotocin. In vitro effects of insulin on rodent acinar cells include stimulation of glucose uptake (19,55), protein synthesis (25,30), potentiation of CCK-induced secretion (1,41), and in pancreas derived AR42J cells, stimulation of mitogenesis (37). At the signal transduction level insulin activates Akt phosphorylation and mTOR signaling (47).…”
Section: Insulin Receptors In the Exocrine Pancreasmentioning
confidence: 99%